Nicorandil ulcer: a frequent diagnosis, a rare etiology - Monteiro, Francisco C.; Oliveira, Pedro J.; Domingues, Bruno F.; Condé, Artur (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2018)
Oral ulcers are a relatively frequent diagnosis in otolaryngology practice. They may have a vast etiology, the iatrogenic medication one of them nicorandil is an anti-ischemic drug used in coronary artery disease and is frequently used in combination with other anti-anginal drugs. There are reports of the association between nicorandil and the appearance of painful oral ulcers, with repercussion on patients’ quality of life. The authors describe a case of a 76-year-old man man with ischemic heart disease past that presented to the emergency department complaining of ulcers on the tongue with 1 week of evolution. He had been medicated with long-standing nicorandil, however he had increased the dose one month before the urge of lesions. He was treated with topical corticosteroid and anti-fungal, with no response. The objective examination showed three ulcerated lesions in the tongue. Given the characteristics of the lesions and absence of response to therapy previously instituted, biopsies were performed. The histopathological results showed nonspecific ulceration aspects. Discussed the case with his Cardiologist and, given the temporal association between increased nicorandil dose and the appearance of the lesions, we decided for the drug suspension. In the revaluation after two weeks, there was favorable evolution, and 45 days after, the lesions had completely disappeared. For the diagnosis of oral ulcers, being of extremely importance to exclude neoplastic causes, it is relevant not to forget also the rarest etiologies, which although difficult to identify, may lead to a better quality of life and less use of medical care.